SIMBOL, MAKNA DAN KONSTRUKSI COPORATE IDENTITY MELALUI LOGO BARU PT. GLOBAL DIGITAL NIAGA (BLIBLI.COM) - Radian Syauqii; Hanny Hafiar; Anwar Sani (SEMIOTIKA: Jurnal Komunikasi, 2017)
This study used qualitative methods to the analysis of semiotics Charles Sanders Peirce. Data was collected by means of media text analysis, documentation and literature. The purpose of this study to know the symbols, meanings and construction of a new corporate identity logo Blibli.com. From the results of research conducted shows that there are scores of new companies that want to add that the best shopping experience and a better life. This value is derived from the vision and mission where Blibli.com want to provide the best shopping experience to consumers, both of life is better perceived by consumers after obtaining the best shopping experience earlier. The impact of this reaseach i can be used to consider about the evaluation step of logo. Advice from researchers, Should Blibli.com conduct a study or evaluation by means of a survey to the community by distributing a questionnaire in order to know how much their level of consciousness or awareness of the meaning of the logo created for the future, meaning that Blibli.com logo can be stuck to the community.Keywords: Semiotics, Charles Sanders Peirce, Logo, Blibli.com